Design and Simulation of Air to Air Missile Homing System - Duhri, Rahmat Alfi; Sasongko, Rianto Adhy; Laksmana, Yayom Dwi (International Series on Interdisciplinary Science and Technology, 2017)
This paper will talk about AIM 120 AMRAAM missile guidance for pursuing a moving target. The missile guidance system itself consists of missile dynamics, control system, seeker, and guidance methods. For general purpose, the missile dynamics approach will use non-linear equation of motions. The control surface that will be discussed follow the rule BTT (Bank-to-Turn) and control system that will be used is PID control system that widely used for control design. Lastly, the guidance method that will be studied here is proportional navigation and constant bearing course approach. The simulation will be conducted using MATLAB Simulink. The Simulink model consist of target dynamics, and guidance system. From the result of simulation, it will be shown that the missile can pursue its target quite well. Hence, the simulation system can be used well for preliminary design purpose.Keywords—Homing System, Control System, Proportional Navigation, Missile Dynamics, Seeker, Bank-to-Turn, Constant Bearing Course.